Digitalization of the banking system: risks and opportunities for managing financial assets - R. G. Nafikov (Управленческие науки)
All sectors of economic activity have changed significantly in globalization, and the banking sector is no exception. Commercial banks around the globe are experiencing digitalization in different ways. However, in the near future, most of these organizations will most likely have to face this process. Otherwise, they simply cannot compete, as the needs of the client base are changing along with continuous technological progress. People are interested in being able to receive services and feedback from the bank quickly and remotely. In order to remain competitive, financial institutions create a new corporate culture, developing and implementing innovative models of interaction with clients. The purpose of the research is to determine the principles of economic security in digitalization of the banking sector and ensure the stability of its functioning, considering possible risks. This study can be useful both for employees of commercial banks for building the processes of digitization of the services provided, and for IT specialists responsible for the development and implementation of certain digital products.